Keragaman Jenis Herpetofauna di Kawasan Hutan Kota Ranggawulung Kota Subang - Mhd Muhajir Hasibuan; Aristyo Dwiputro; Siti Rabiatul Fajri; Rizki Kurnia Tohir (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Ranggawulung City Forest is a Green Open Space (RTH) located in Subang City. As one of the remaining forests in the middle of an urban area, this urban forest has great potential as a location for biodiversity management. This research was conducted to determine the value of biodiversity, especially herpetofauna in Ranggawulung City Forest, Subang City as an indicator for evaluating the success of environmental management in the future. This study uses the Visual Encounter Survey (VES) method modified with Time Search. The herpetofauna diversity (H') in general observed in the Ranggawulung City Forest was 2.59 in the HKR block, and 2.34 in the Buper block. The value of species richness (Dmg) in each block is 4.41 and 3.40. The two areas are relatively evenly distributed with an evenness value of more than 80%. There were no nationally protected species of herpetofauna, two of which were species whose trade was restricted internationally and were included in the CITES Appendix II category.